THE CHILD'S VIEW OF THE TERRITORY: PERSPECTIVES FOR CHILD DEVELOPMENT - Oliveira, Fernanda Anjos de; Palombo, Claudia Nery Teixeira; Silva, Melissa Almeida; Oliveira, Clariana Vitória Ramos de (Cogitare Enfermagem, 2024)
Objective: to understand children's perspective on the territory in which they live. Method: a qualitative study carried out at a public university in northeastern Brazil in July 2023. Interviews with 15 children aged between seven and 12 were conducted after parental authorization and the children's consent. Content analysis used the Territorial Impact Dimensions model as a theoretical framework: Physical, Socioeconomic, Services, Social Network, and Governance. Results: the children recognize poverty (Socioeconomic Dimension), violence (Social Network Dimension), and the precariousness of the physical structure of the neighborhoods (Physical Dimension). Living with neighbors/friends (Social Network Dimension), the school (Services Dimension), and the playgrounds (Physical Dimension) make it easier to cope with the problems. They call for greater efforts from government officials to improve the area. Final considerations: considering the child's perspective shows respect and encourages their active role in planning strategic actions, favoring the effectiveness of actions to promote child health.